Association of Circulating, Inflammatory-Response Exosomal mRNAs With Acute Myocardial Infarction - He, Guo-dong; Huang, Yu-qing; Liu, Lin; Huang, Jia-yi; Lo, Kenneth; Yu, Yu-ling; Chen, Chao-lei; Zhang, Bin; Feng, Ying-qing (Frontiers in Cardiovascular Medicine, 2021)
Background: although many cardiovascular disease studies have focused on the microRNAs of circulating exosomes, the profile and the potential clinical diagnostic value of plasma exosomal long RNAs (exoLRs) are unknown for acute myocardial infarction (AMI). Methods: in this study, the exoLR profile of ten AMI patients, eight stable coronary artery disease (CAD) patients, and ten healthy individuals was assessed by RNA sequencing. Bioinformatic approaches were used to investigate the characteristics and potential clinical value of exoLRs. Results: exosomal mRNAs comprised the majority of total exoLRs. Immune cell types analyzed by CIBERSORT showed that neutrophils and monocytes were significantly enriched in AMI patients, consistent with clinical baseline values. Biological process enrichment analysis and co-expression network analysis demonstrated neutrophil activation processes to be enriched in AMI patients. Furthermore, two exosomal mRNAs, ALPL and CXCR2, were identified as AMI biomarkers that may be useful for evaluation of the acute inflammatory response mediated by neutrophils. Conclusions: exoLRs were assessed in AMI patients and found to be associated with the acute inflammatory response mediated by neutrophils. Exosomal mRNAs, ALPL and CXCR2, were identified as potentially useful biomarkers for the study of AMI.